Turning eco-investments into sustainable competitive advantages: an exploratory case study of eco-oriented startup - Ratna Pratama; Sari Wahyuni (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Many studies have been conducted to understand eco-investment contribution on firms’ competitive advantages but there are still limited studies about its effects on eco-oriented startups’ competitive advantages. This qualitative study is written to explore more in detail on eco-oriented startups process in gaining sustained competitive advantages from their eco-investments. Using an existing conceptual framework for sustainability strategies, this single case study probes into a B corporation certified startup and found that eco-investments contribute to support the eco-oriented startup in gaining sustainable competitive advantages in multiple ways. The process can be categorized into three stages. First, eco-investments improve attractiveness of the company in eyes of investors and improve the likelihood to get funding from multiple funding sources. Second, eco-investments improve job satisfaction, motivation and employees’ sense of belonging. Lastly, eco-investments and eco-innovation support the company in executing eco-branding and beyond compliance leadership strategies but without sustainable value innovation, the startup can only achieve temporary competitive advantages not sustainable competitive advantages. The findings presented here may help startup founders and other business practitioners, especially those who are responsible in creating business strategy, to evaluate their eco-investment decisions based on the company's resources and capability in order to obtain sustainable competitive advantages.